The influence of subsistence strategy and climate on bony labyrinth morphology in recent Homo sapiens. Issue 3 (4th January 2022) - Ward, Devin L.; Schroeder, Lauren; Roy, Jocelyn E.; Hertz, Madelyn; Uhl, Alexandra; Pomeroy, Emma; Stock, Jay T.; Copes, Lynn; Baab, Karen L.; Viola, T. Bence; Silcox, Mary T.
Abstract: Objectives: Intraspecific shape variation in the recent Homo sapiens bony labyrinth has been assessed for association with sexual dimorphism, body size, and genetic differences, but has not been fully assessed for association with extrinsic factors, such as subsistence strategy and climate. While the skull overall is known to vary with these variables, the bony labyrinth develops in utero and exhibits microstructural stability through adulthood. Therefore, labyrinthine morphology may be resistant to extrinsic variables. Materials and methods: We collected labyrinthine shape data using computed tomography from 262 individuals associated with archeological or contemporary collections used for dissection in North America, Europe, Africa, and Southeast Asia. We assessed the data for observer error and asymmetry. Shape variation is examined between subsistence strategy groups and climate type groups with Principal Components Analyses and Procrustes ANOVA's, and shape variation was correlated with specific climate data (precipitation, temperature, altitude) with a two‐block partial least squares analysis. Results: Both inter‐ and intra‐observer error as well as asymmetry minimally affected labyrinthine shape variation. We found that both subsistence strategy and climate each account for a statistically significant 7% of overall shape variation, and that specific climate variables have statistically significant correlation with labyrinthine shape variation (RV 0.52527). Discussion: Morphological variation in this sample indicates that the labyrinth is not entirely resistant to extrinsic factors associated with subsistence strategy and climate. Shape differences are not localized to specific regions of the labyrinth, but may contribute to the complicated variation seen in recent human evolution and warrants further exploration. Abstract : The recent human bony labyrinth within the cranium (A) and segmented from the cranium (B) using computed tomography.